Pendampingan Perancangan dan Deteail Engineering Design (DED) Gedung Serbaguna PCM Sawit Boyolali - Guntur Nugroho; As'at Pujianto; Yoga Aprianto Harsoyo; Fathurrahman Kamal; Gita Danu Pranata; Ghoffar Ismail; Chusnul Azhar; Arini Hidayah; Ulfah Dian Indriyani (Universitas Muhammadiyah Manado, 2024)
The Community Service Program (PkM) titled